Radiotherapy-induced dynamic changes in the lymphocyte-to-monocyte ratio in patients with laryngeal cancer indicate poor prognosis - Cichowska-Cwalińska, Natalia; Bieńkowski, Michał; Popęda, Marta; Dróżka, Magdalena; Rutkowski, Jacek; Jassem, Jacek; Zaucha, Renata (Frontiers in Oncology, 2023)
We hypothesized that markers of inflammation correlate with response to radiotherapy in patients with non-metastatic laryngeal cancer (LC). Our aim was to assess peripheral and local markers of inflammation including lymphocyte to monocyte ratio (LMR), neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), infiltrating CD8+ lymphocytes (TILsCD8), and programmed death 1 ligand (PD-L1) expression.We performed a retrospective single-center analysis of LC patients administered definitive (R-RT) or postoperative radiotherapy (PORT). The primary endpoint was overall survival (OS) in relation to peripheral and local inflammatory markers and their dynamic changes during RT.Results: Study group included 215 patients (R-RT, n=116; PORT, n=99). The baseline (t0) NLR and LMR were significantly correlated with OS in the R-RT group. In patients with high and low NLR at t0, the five-year OS was 33% and 56% (p=0.010) and in high and low LMR at t0, the five-year OS was 56% and 27% (p=0.003), respectively. The LMR increase during R-RT predicted better prognosis: the five-year OS in high and low LMR was 57% and 31% at t2 (after 2 weeks of RT) (p=0.015), 49% and 26% at t4 (p< 0.001), and 50% and 25% at t6 (p=0.013), respectively. Multivariable analysis shows that the worse performance status (p=0.003), the presence of nodal metastases (p=0.0001), and low baseline LMR (p=0.049) in the R-RT group, and the presence of nodal metastases (p=0.035) and completion treatment on time (p=0.042) in PORT group were associated with poor prognosis. The PD-L1 expression had no significant prognostic value in any of the examined patients.The baseline LMR and its dynamic changes during R-RT and baseline NLR are independent prognostic factors in patients with nonmetastatic LC. PD-L1 expression and number of TILsCD8 have no prognostic value in R-RT and PORT group.